Can there be too much information? Heterogeneous responses to information on benefits from language proficiency - Fabian Könings (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2021)
Immigrants who have a better command of the host country's language are more likely to be employed and earn higher wages. Using a survey experiment among international students in Germany, I investigate whether information on the monetary benefits of mastering the language of the host country influences the intention to learn that language. The results show heterogeneous responses conditional on the current level of German language proficiency. The intended participation of international students with high German language skills is not affected, students with medium German language skills are positively affected and those with low or no German language skills are negatively affected. For policy makers, seeking to increase the level of language proficiency, this surprising negative effect suggests that there can be too much information.
Keywords: D01; F22; J24; O15; 330; language learning; information experiment; migration; international students